Determining range edges: habitat quality, climate or climate extremes?. Issue 1 (18th November 2013) - Seabrook, Leonie; McAlpine, Clive; Rhodes, Jonathan; Baxter, Greg; Bradley, Adrian; Lunney, Daniel; Thuiller, Wilfried
Abstract Aim Climate change is predicted to adversely affect wildlife populations at the trailing edge of their range, with extreme weather events acting as a catalyst for local extinctions and range contractions. We assessed the relative importance of long‐term climate averages, short‐term drought and habitat in predicting species occupancy and range edge, using the koala (Phascolarctos cinereus) as a case study. Location Queensland, Australia. Methods We used mixed effects models to quantify the influence of habitat quality and climate on koala distribution at the trailing edge of their range, at three spatial scales. We used piecewise logistic regression to estimate thresholds in the relationship between the range edge and key environmental variables. Results Both climatic and habitat variables explained koala presence. At the site scale, the quality of habitat was important within landscapes that had experienced higher levels of rainfall during a decade‐long drought. The spatial pattern of the koala's present‐day western range limit reflects closely a breakpoint of 350 mm in summer rainfall during the drought years, supporting both theoretical predictions and empirical research on the influence of climate extremes on contracting edge populations. Main conclusions The distribution of fauna at their range margin in semi‐arid regions reflects extreme climate events, such as drought. Within suitable climate conditions, habitat quality is important in determining site occupancy. The identification and protection of habitat refugia, where local microclimates and habitat characteristics can mitigate the impacts of extreme events on fauna species at the contracting edge of the range, may allow species to persist for longer under changing climate conditions.